2023
DOI: 10.2147/ijgm.s428709
|View full text |Cite
|
Sign up to set email alerts
|

Identification of Oxidative Stress-Related Biomarkers in Acute Myocardial Infarction

Yihan Sun,
Min Wang,
Xi Tan
et al.

Abstract: Purpose Acute Myocardial Infarction (AMI) is globally prevalent, with oxidative stress as a key contributor to its pathogenesis. This study aimed to explore oxidative stress-related genes as potential AMI biomarkers, elucidating their role in disease progression. Patients and Methods Gene expression data from AMI samples in the Gene Expression Omnibus (GEO) database and oxidative stress-related genes (OSRGs) from the GeneCards database were extracted. Weighted Gene Co-e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 24 publications
0
2
0
Order By: Relevance
“…Primarily secreted by neutrophils, S100A12 interacts with the receptor for advanced glycation end products, implicated in atherosclerosis and cardiovascular diseases [ 27 , 28 ]. Prior studies consistently reported elevated S100A12 levels in the plasma of STEMI patients, suggesting its potential as an early-stage prognostic biomarker [ 29 ]. Our findings align with existing research, demonstrating significant upregulation of S100A12 in the serum of STEMI patients [ 11 , 29 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Primarily secreted by neutrophils, S100A12 interacts with the receptor for advanced glycation end products, implicated in atherosclerosis and cardiovascular diseases [ 27 , 28 ]. Prior studies consistently reported elevated S100A12 levels in the plasma of STEMI patients, suggesting its potential as an early-stage prognostic biomarker [ 29 ]. Our findings align with existing research, demonstrating significant upregulation of S100A12 in the serum of STEMI patients [ 11 , 29 ].…”
Section: Discussionmentioning
confidence: 99%
“…Prior studies consistently reported elevated S100A12 levels in the plasma of STEMI patients, suggesting its potential as an early-stage prognostic biomarker [ 29 ]. Our findings align with existing research, demonstrating significant upregulation of S100A12 in the serum of STEMI patients [ 11 , 29 ]. This upregulation may result from neutrophil activation, chemotaxis, and release triggered by STEMI [ 30 ].…”
Section: Discussionmentioning
confidence: 99%